3D conductive CNTs anchored with Na2FeSiO4 nanocrystals as a novel cathode material for electrochemical sodium storage. Issue 17 (1st December 2018) - Feng, Zaiqiang; Tang, Mingqi; Yan, Zhenwei
Abstract: Sodium iron silicate (Na2 FeSiO4 ) has been investigated as a novel cathode material for electrochemical sodium storage due to the abundance of Na and Fe resources, good structure stability and high theoretical capacity. Herein, we report a simple strategy for fabricating the 3D CNTs-decorated Na2 FeSiO4 microspheres through a facile spray-drying method. Inside the microspheres, the Na2 FeSiO4 nanocrystals are anchored on the CNTs, forming the conductive transport pathways for electrons and Na + -ions. This cathode exhibits a high specific capacity of 168.7 mAh g −1 at 0.1 C and also shows excellent cycling performances at high current rates. Therefore, the as-fabricated 3D composite is an advanced electrode for rechargeable sodium-ion batteries.